(untitled) (Economics and region, 2025)
The article explores the theoretical and methodological foundations of forming regional competitiveness in Ukraine under the conditions of post-war transformation. The authors emphasize that regional competitiveness is a key factor in ensuring sustainable socio-economic growth and plays a central role in rebuilding the country after large-scale armed aggression. The study highlights the importance of a balanced combination of natural, acquired, and controllable factors that influence the competitive positions of regions. A systematic classification of these factors is proposed, based on the strength and nature of their impact on the integral competitiveness index. The article introduces a structured approach to assessing regional resilience and the potential for recovery, taking into account the losses caused by the war, including destruction of infrastructure, demographic shifts, and security risks. Particular attention is paid to the role of human capital development, innovation, technological modernization, and institutional support in enhancing regional competitiveness. Furthermore, the article presents a cluster-based methodology for categorizing Ukrainian regions according to their pre-war economic and social development levels and their current needs in terms of recovery spending. The research underlines the transformation of regional priorities, the revision of traditional economic strategies, and the need for innovative models of territorial development. These models must integrate economic instruments with national security strategies to ensure long-term sustainability and adaptability in the face of continuous uncertainty and external threats. The authors also analyze the influence of intangible resources – such as knowledge, innovation, and social capital – on the sustainable growth of regions, underlining the paradigm shift from traditional resource-based competitiveness to one based on knowledge and resilience. The findings of the study are practically significant for policymakers, local governments, and development institutions, as they provide a strategic framework for designing adaptive recovery strategies. In conclusion, the article contributes to the scientific discourse on regional development by offering a comprehensive framework for evaluating and strengthening the competitive advantages of Ukrainian regions in the context of post-conflict reconstruction and future-oriented planning.